Financial provision ofhousehold food security (World of finance, 2019)
Introduction. The issue of providing humanity with food rightly holds one of the leading places in the hierarchy of global problems. Food safety of a country is an indispensable condition and guarantees its sovereignty and independence, ensuring its sustainable social and economic development, population’s high level and quality oflife and reproduction ofhuman capital.The purpose of the article is to assess the state of food security of Ukraine, the definition of the role of households in ensuring food security and the justification of directions for improving financial leverage in the context of the implementation of Ukraine’s agricultural and food potential.Main results of the study. For Ukraine, the problem of ensuring food security is of particular importance, which is conditioned by the current state of development of the domestic agricultural and industrial complex, the increase of production in which is carried out mainly by an extensive way.The most important conditions for achieving food security are: the potential physical availability of food for every person; economic opportunity of purchasing food by all social groups of the population, including disadvantaged ones, which is achieved by raising the standard of living or implementing the necessary measures of social security; consumption of high quality products in quantities sufficient forrational nutrition.In order to increase the food security financial support, it is necessary to improve the financial component of the comprehensive food security mechanism, which aims at ensuring the application of economic instruments and creating conditions for attracting monetary resources for the functioning ofthe food security system through the creation of amulti-channel financing system.Conclusions. Therefore, the main directions of improving the financial system for the purpose of ensuring food security ofthe country are: availability of financial and credit support to agricultural producers; introduction of innovations in agricultural production; regulation of conditions for foreign and domestic food trade through a system of tariff and non-tariff instruments; systemic measures to strengthen and extend the life expectancyofthe population, wages and salaryincrease.